SUVN‐I6107: A novel muscarinic M1 receptor‐positive allosteric modulator (M1‐PAM) for the treatment of cognitive deficits: Biomarkers (non‐neuroimaging)/Prognostic utility. (7th December 2020) - Abraham, Renny; Goura, Venkatesh; Grandhi, Venkata Ramalingayya; Tadiparthi, Jayaprakash; Ganuga, Narender; Medapati, Rajesh Babu; Muddana, Nageswara Rao; Palacharla, Veera Raghava Chowdary; Bhyrapuneni, Gopinadh; Bojja, Kumar; Mekala, Venkat Reddy; Srirangavaram, Maheswari; et al.
Abstract: Background: Muscarinic acetylcholine receptors (mAChRs) belong to family of G protein coupled receptors (GPCRs) which are widely expressed throughout the body. Muscarinic receptors have been implicated in the pathophysiology of various central nervous system disorders. M1 muscarinic receptor subtype plays a vital role in cognition, attention mechanisms and sensory processing. Discovery and development of selective M1 muscarinic ligands have been largely unsuccessful mainly due to high conservation of the orthosteric binding site among this receptor family. Thus, ligands that positively modulate the less conserved M1 muscarinic allosteric site may be advantageous over the orthosteric agonists Method: SUVN‐I6107 is a lead compound from the M1 positive allosteric modulator (PAM) program. The effects of SUVN‐I6107 on the allosteric site of the M1 receptor was evaluated using the reporter gene assay. In addition, binding potential towards the orthosteric site across the muscarinic receptor subtypes was also studied. The pharmacokinetic properties of SUVN‐I6107 were studied both in rodent and non‐rodent species. The pro‐cognitive potential of SUVN‐I6107 was studied in diverse models of learning and memory. The safety of SUVN‐I6107 was assessed using in‐vitro and in‐vivo systems. Result: SUVN‐I6107is a selective M1‐PAM with no agonistic activity across the muscarinic receptor subtypes. SUVN‐I6107 has good oral bioavailability in animal models. It also has excellent brain penetration with adequate protein free fraction. SUVN‐I6107 reversed the time induced memory deficit in the object recognition task. It also attenuated the scopolamine induced memory deficits in the object recognition as well as the contextual fear conditioning task. SUVN‐I6107 enhanced the cerebral blood flow in rats, potentiated the effects of donepezil, and promoted non‐amyloidogenic APP processing in rats. SUVN‐I6107 did not have the side effects associated with the stimulation of the cholinergic system. SUVN‐I6107was found to be safe in the cardiovascular safety assays and early stage animal toxicity studies. Conclusion: SUVN‐I6107is a novel, selective and potent M1‐PAM, demonstrating efficacy in animal models and devoid of cholinergic side effects.